PENGARUH MANAJEMEN KELAS DAN PERILAKU BELAJAR TERHADAP HASIL BELAJAR MATA PELAJARAN IPS KELAS VIII DI UPTD SMP NEGERI 4 PEMATANGSIANTAR - Mella Senteria Manalu; Susy Alestriani Sibagariang; Anton Luvi Siahaan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This quantitative research using an ex post facto method aims to analyze the influence of classroom management and learning behavior on the social studies learning outcomes of eighth-grade students at the UPTD SMP Negeri 4 Pematangsiantar, both partially and simultaneously. Based on the philosophy of positivism, the data were analyzed using statistical regression techniques. The study showed that both independent variables significantly influenced learning outcomes. The regression analysis yielded a coefficient of determination (R-square) of 0.760, indicating that 76% of student learning outcomes can be explained by classroom management and learning behavior, while the remaining 24% is influenced by other factors outside the study. The adjusted R-square of 0.757 indicates that the research model has strong ability to explain the dependent variable. Furthermore, the correlation coefficient (R-square) of 0.872 indicates a very strong relationship between classroom management and learning behavior and students' social studies learning outcomes.